2022
DOI: 10.1097/wnr.0000000000001795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rg1 on proliferation and directed differentiation of human umbilical cord mesenchymal stem cells into neural stem cells

Abstract: Objective Human umbilical cord mesenchymal stem cells (hUCMSCs) can be transformed into neural stem cells (NSCs) and still maintain immunomodulatory and antioxidant effects. Transplantation of NSCs induced by hUCMSCs would be a promising therapeutic strategy for the treatment of neurological diseases. Ginsenoside Rg1 has neuroprotective effects and influences cell proliferation and differentiation. In this study, we further evaluated the effects of ginsenoside Rg1 on the proliferation and directiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…58 The neuroprotective effect of ginsenosides may be related to the MAPK, PI3K/AKT, cyclin-dependent kinase 5, BDNF/ TrkB, protein kinase A/cAMP-response element binding protein (CREB), fibroblast growth factor 2 (FGF2)/AKT, NF-κB, nod-like receptor protein1, N-methyl-D-aspartate receptor 2B/ ERK (extracellular regulated protein kinase)/CREB/BDNF, notch, Wnt/β-catenin, toll-like receptor-3 (TLR3), and TLR4 signaling pathways. 45,59,60 Ginsenosides could improve various nervous system diseases (Table 1). For instance, ginsenoside Rg1 curtailed oxi- Food & Function Review dative stress, minimized neuro-inflammation and safeguarded neurons by regulating the GSK-3β/Wnt pathway, thereby improving cognitive impairment in Alzheimer's disease (AD).…”
Section: Role In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…58 The neuroprotective effect of ginsenosides may be related to the MAPK, PI3K/AKT, cyclin-dependent kinase 5, BDNF/ TrkB, protein kinase A/cAMP-response element binding protein (CREB), fibroblast growth factor 2 (FGF2)/AKT, NF-κB, nod-like receptor protein1, N-methyl-D-aspartate receptor 2B/ ERK (extracellular regulated protein kinase)/CREB/BDNF, notch, Wnt/β-catenin, toll-like receptor-3 (TLR3), and TLR4 signaling pathways. 45,59,60 Ginsenosides could improve various nervous system diseases (Table 1). For instance, ginsenoside Rg1 curtailed oxi- Food & Function Review dative stress, minimized neuro-inflammation and safeguarded neurons by regulating the GSK-3β/Wnt pathway, thereby improving cognitive impairment in Alzheimer's disease (AD).…”
Section: Role In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The neuroprotective effect of ginsenosides may be related to the MAPK, PI3K/AKT, cyclin-dependent kinase 5, BDNF/TrkB, protein kinase A/cAMP-response element binding protein (CREB), fibroblast growth factor 2 (FGF2)/AKT, NF-κB, nod-like receptor protein1, N -methyl- d -aspartate receptor 2B/ERK (extracellular regulated protein kinase)/CREB/BDNF, notch, Wnt/β-catenin, toll-like receptor-3 (TLR3), and TLR4 signaling pathways. 45,59,60…”
Section: Ginsenosidesmentioning
confidence: 99%
“…Ginsenoside Rg1 promotes the neural phenotype differentiation of human ADSCs by activating the expression of NSC niche components including growth associated protein-43 (GAP-43), neural cell adhesion molecule (NCAM), and synapsin-1 (SYN-1) ( Xu et al, 2014 ). In addition, ginsenoside Rg1 promotes the differentiation of human umbilical cord mesenchymal stem cells (hUCMSC) into NSCs by downregulating genes involved in the Wnt/β-catenin and Notch signaling pathways, including GSK3β, β-catenin, Notch1, and Hes1 ( Xiao et al, 2022 ). However, the transdifferentiation capability of NSCs is still doubted since the possible contamination by other tissue stem cells or embryonic stem cells in those studies.…”
Section: Effects Of Ginseng On Different Types Of Stem Cellsmentioning
confidence: 99%
“…One research group found that the main therapeutic effects of ginsenoside Rb1 were anti-platelet and anti-vascular remodeling activities (Xiang et al, 2020). Ginsenoside Rb1 has been focused on for the mechanism of prevention and treatment of atherosclerotic embolism (Wang et al, 2021;Xiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%